Simple Financial Report Recording Training for Snack Food MSMEs in Tunggara Village: Pelatihan Pencatatan Laporan Keuangan Sederhana Untuk UMKM Makanan Ringan Di Desa Tunggara - Tri Cahyani; Yudas Tadius Andi Candra (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
MSMEs in Indonesia often face difficulties in implementing accounting practices because they think it is too complicated. Even so, MSME players still get profits but they are not measured accurately. The aim of this community service activity is to provide training in recording simple financial reports to MSMEs. The MSME sector chosen as a place for community service activities is two business actors in the snack food sector located in Tunggara Village, Banjarnegara Regency. The methods used in this competition are preparation, training and implementation. After carrying out the service, an evaluation is carried out by comparing the results before and after the activity. The activity was carried out for five days in August 2023. The final results of this service activity show that MSME players are able to record financial reports simply and can see the profits obtained more accurately each month.